2021
DOI: 10.1108/jbsed-03-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Political ties and corporate performance: why efficiency matters?

Abstract: PurposeThe purpose of this paper is to examine and explain the complex interrelationships which influence the performance of politically connected firms to create value for their providers of finance and other stakeholders. In doing so, it examines the interrelationships between efficiency and delivering on corporate performance of a firm with political ties.Design/methodology/approachThe authors gathered the literature from the Scopus website. They reviewed the literature of 58 manuscripts about the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 68 publications
3
25
0
2
Order By: Relevance
“…This result is also found the increase of ROA on firms when non-politically experience personnel is to replace with someone with political ties (Bertrand et al, 2007;Ding et al, 2014). To add, this result is consistent with prior study that also found the firm performance using the ROE as indicators shows a tremendous result with strong government participation (Guerra Pérez et al, 2015;Hashmi et al, 2018;Hong, 2010;Najaf, 2021). Politicians may be able to assist terms of policy and law implementation, allowing for faster decision-making and are capable of strategic action to adapt for economic conditions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result is also found the increase of ROA on firms when non-politically experience personnel is to replace with someone with political ties (Bertrand et al, 2007;Ding et al, 2014). To add, this result is consistent with prior study that also found the firm performance using the ROE as indicators shows a tremendous result with strong government participation (Guerra Pérez et al, 2015;Hashmi et al, 2018;Hong, 2010;Najaf, 2021). Politicians may be able to assist terms of policy and law implementation, allowing for faster decision-making and are capable of strategic action to adapt for economic conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Our paper reconciles positive findings suggest that the interventions bring fortunate steps for company in order to survive in the volatility of oil prices that were inherently tied to the low responsiveness of both demand and supply in the short run compared with other commodities. Align with the resource-based value (RBV) theories, CPCs able to capture good return and able to balance the lag between investment and production (Najaf, 2021). For instance, the process of oil and gas includes a wide range of operation and equipment that generating pollution, disrupting wildlife and damaging public lands.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as highlighted in Atayah et al (2021b), corporate risk-taking behavior depends on the top executives’ experience and preferences to handle risk management strategies. Najaf and Najaf (2021a) discuss the role of government entities in developing sustainable strategies at the corporate level. Thus, the government must implement and revive public policies to promote sustainability.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…From a more strategic perspective, stakeholders believe that activities related to environmental and social sustainability might improve their firm's financial claims (Sahasranamam et al, 2020). Alternatively, sustainability is a feasible strategy for meeting stakeholders' requirements but must not interfere with the firm's primary goal (Najaf, 2021).…”
Section: Stakeholders Theorymentioning
confidence: 99%